2010
DOI: 10.1039/b919993d
|View full text |Cite
|
Sign up to set email alerts
|

Chirality transition in the epoxidation of (−)-α-pinene and successive hydrolysis studied by Raman optical activity and DFT

Abstract: Characterization of the chirality evolution involved in chemical and biochemical reaction processes is extremely important to the understanding of the chiral catalysis mechanism. In this work, the chiral transition from the epoxidation of (-)-alpha-pinene to alpha-pinene oxide and successive hydrolysis to (-)-pinanediol has been studied as an archetype of the asymmetric catalysis by Raman optical activity (ROA) and the DFT calculation. Minor changes of the absolute configuration of the chiral products from (-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…All these bands are associated with the scissoring vibrations of-CH 2 groups and the antisymmetric-CH 3 deformations and reflect the chiral environment in the bycyclic ring structure. [38] It seems that, in the experimental spectrum, there are also other noticeable features similar to those reported in the literature, such as positive peaks at 1165, 1197 and 1208 cm −1 (corresponding to theoretical bands at 1169, 1202 and 1214 cm −1 , respectively). According to our calculations, the origin of the band at 1165 cm −1 with a large positive ROA activity is the combination of predominant wagging vibrations localized at two chiral centres, that is the C 4 and C 1 carbon atoms.…”
Section: Raman and Roa Spectra Of Bornyl Acetatesupporting
confidence: 62%
See 1 more Smart Citation
“…All these bands are associated with the scissoring vibrations of-CH 2 groups and the antisymmetric-CH 3 deformations and reflect the chiral environment in the bycyclic ring structure. [38] It seems that, in the experimental spectrum, there are also other noticeable features similar to those reported in the literature, such as positive peaks at 1165, 1197 and 1208 cm −1 (corresponding to theoretical bands at 1169, 1202 and 1214 cm −1 , respectively). According to our calculations, the origin of the band at 1165 cm −1 with a large positive ROA activity is the combination of predominant wagging vibrations localized at two chiral centres, that is the C 4 and C 1 carbon atoms.…”
Section: Raman and Roa Spectra Of Bornyl Acetatesupporting
confidence: 62%
“…Thus, among others, we can see in these spectra characteristic bands at 1688, 1659 and 1639 cm −1 due to C C stretchnig vibrations originating from 3-carene, α-pinene and probably camphene, respectivety, and well-structured marker bands for these components attributed to ring deformations at 669 cm −1 for α-pinene or 717 cm −1 for 3-carene. [12,35,38,39,41] However, above all, we are able to define several characteristic key bands for BA, which do not overlap with other principal component bands of pichtae oil (Fig. S2), including those at 1736, 1049, 839, 746, 657, 642 and 591 cm −1 described earlier (text or Table 1).…”
Section: Raman and Roa Spectra Of Pichtae Essential Oilmentioning
confidence: 92%
“…In addition, attention may need to be paid if judging the strongest peak at 1644 cm À1 (C5 5C stretching) [39] as it also allows for peakvalue shifts according to the calculation results in this study. It is worth mentioning that the fruitful Raman peaks as a whole could still be a piece of evidence to recognize the presence of b-pinene and even likely its proportion of ingredients.…”
Section: Resultsmentioning
confidence: 98%
“…First glance could focus on the 644 cm À1 mode (ring breathing) in the experimental Raman spectrum which allows a red-shift of $14 cm À1 (i.e., a peak at 630 cm À1 ) by comparing the theoretically predicted Raman activity. It is suggested that the series of peaks at 1413 cm À1 (CH 2 scissoring), 1439 cm À1 (CH 2 scissoring), 1458 cm À1 (CH 2 scissoring, CH 3 asymmetric deformation) and 1478 cm À1 (CH 2 scissoring, CH 3 asymmetric deformation) [39] could be regarded as another fingerprint of b-pinene.…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45][46] As a given chiroptical spectroscopic method may not give complete and entirely correct structural information for a given molecule, the simultaneous use of more than one spectroscopic method may provide the complete information. [62][63][64][65] The chiroptical variant of Raman scattering, ROA, is proven to be an effective tool to determine the configuration, conformation, and behavior of chiral molecules in recent years, 43,45,[66][67][68][69][70][71][72][73][74][75][76] and thus a presumably good candidate for the study of sulfur chirality. 48 The high polarizability of sulfur atom makes Raman spectroscopy a sensitive technique to identify sulfur compounds, and much effort has been focused on correlation between C-S, S-S stretching modes and the S-S dihedral angle.…”
Section: Introductionmentioning
confidence: 99%